Islamophobia, mental health and psychiatry: South Asian perspectives - Roy A. Kallivayalil (Eco-Vector, 2020)
Asia is the largest and the most populous continent on earth. South Asia has a population of around 1.8 billion,thus constituting about one fourth of humanity. India, Pakistan, Bangladesh, Sri Lanka, Nepal, Bhutan, the Maldivesand Afghanistan are the countries in South Asia and many of them are Muslim-majority nations. Although Indiais predominantly a Hindu nation with a total population of 1.4 billion, there are more Muslims in India than in Pakistanand other South Asian nations. Hindus, Muslims, Christians, Sikhs and followers of other religions have lived peacefullyin South Asia for centuries. However, certain incidents of communal violence and other untoward occurrences in SouthAsia suggest that Islamophobia is present here too. The authors discuss demography, cultures and the possible effectof Islamophobia on the mental health of the people of South Asia.